2004
DOI: 10.1111/j.1600-6143.2004.00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Prophylaxis and Graft Outcome in Solid Organ Transplantation: A Collaborative Transplant Study Report

Abstract: We investigated relationships between cytomegalovirus (CMV) seropairing and CMV prophylaxis on graft outcome in recipients of solid organ transplants. Transplants carried out from 1985 to 2002 and reported to the Collaborative Transplant Study were analyzed. In cadaver kidney recipients, CMV prophylaxis was significantly associated with improved graft survival only in the seronegativerecipient/seropositive-donor combination (at 3 years: 79.4% with prophylaxis vs. 73.5% without prophylaxis; RR 0.80, p < 0.0001)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
120
2
11

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(145 citation statements)
references
References 42 publications
12
120
2
11
Order By: Relevance
“…Both direct and indirect effects are often present simultaneously, and the relative clinical contributions of any of these mechanisms are uncertain. In general, CMV seropositivity and receipt of seropositive organs and viremia are linked in many, but not all, studies to diminished long-term graft function (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Furthermore, most studies have indicated that successful antiviral prophylaxis has a beneficial effect on long-term graft function (8).…”
Section: Introductionmentioning
confidence: 99%
“…Both direct and indirect effects are often present simultaneously, and the relative clinical contributions of any of these mechanisms are uncertain. In general, CMV seropositivity and receipt of seropositive organs and viremia are linked in many, but not all, studies to diminished long-term graft function (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Furthermore, most studies have indicated that successful antiviral prophylaxis has a beneficial effect on long-term graft function (8).…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for CMV infection/disease include CMV donorpositive/recipient-negative (D+/R-) serostatus pairs, recent treatment for acute rejection, recent completion of prophylactic antiviral therapy, and rabbit anti-thymocyte globulin induction therapy [53,54]. In CMV D+/R-pairs, there may be an association between the use of CMV prophylaxis and improved graft survival and lower acute rejection rates [55].…”
Section: Cytomegalovirusmentioning
confidence: 99%
“…Nevertheless, we must acknowledge that long-term data on allograft loss, maternal survival after pregnancy (due to an increased risk of viral diseases and neoplasm secondary to immunosuppressants) 15 and offspring outcomes of transplant recipients is rather limited. Despite several reports indicating no increase of congenital anomalies among the offspring of recipients, 14,16 long-term outcomes focusing on physical and mental development, and immunological and oncological pathologies later in life in these offspring is necessary.…”
Section: -14mentioning
confidence: 99%